Public Engagement for Regulatory Reform: A Case Study of Autologous Stem Cell Therapy Regulation in Australia. Issue 5 (October 2019) - Dempster, Georgia; Sutherland, Georgina; Keogh, Louise
As a method of science communication, public consultations have the potential to offer members of society the opportunity to influence government policy. An important component of public consultations is the evaluation of stakeholder submissions (from individuals to large organizations). As a case study, we investigated an Australian public consultation on the regulation of autologous stem cell therapies (ASCT) facilitated by the Therapeutic Goods Administration. Our results showed a divide between stakeholders who wanted ASCT to remain unregulated and stakeholders who wanted ASCT to become regulated. Since the consultation, the Therapeutic Goods Administration has decided to implement stringent regulation of most ASCT.